Heritage of Pranas Mašiotas (1863–1940): expression and development of the history of mathematics in Lithuania - Banionis, Juozas (Lietuvos matematikos rinkinys, 2014)
The science of mathematics played an important role in Pranas Mašiotas’ life. It was not just a coincidence because Pranas Mašiotas graduated from the Faculty of Mathematics and Physics of Moscow University. In the process of reinforcing the notion of modern mathematical education in Lithuania, P. Mašiotas put an emphasis on the importance of the science of mathematics which could insure interdisciplinary relations among different subjects in the curriculum. Pranas Mašiotas’ activity was not left without attention. He was awarded an Honorary Doctor’s Degree on his 60th jubilee. The degree was conferred by the initiative of the Faculty of Mathematics and Natural Sciences of Lithuanian University on the 17 of December 1923.